1984
DOI: 10.1093/carcin/5.12.1577
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of benzo[a]pyrene by cultured human hepatocytes from multiple donors

Abstract: Primary hepatocyte cultures from six human donors were established and their abilities to metabolize the polycyclic aromatic hydrocarbon carcinogen benzo[a]pyrene (B[a]P) were examined. Cells from each donor were plated at similar densities (1 X 10(7) cells/100 mm dish). All cultures metabolized B[a]P to a significant extent (24-35 nmol in 24 h) and h.p.l.c. profiles of the organic solvent-soluble and glucuronidated B[a]P metabolites were obtained for all donors. The predominant extracellular organic solvent-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The longer duration of the testing was due to the limited availability of cells from human donors with acceptable demographics and CYP3A activity. During the course of this study, we observed substantial donor-to-donor variability in CYP3A activity (data not shown), consistent with previous literature (Moore and Gould, 1984). In addition, the cost of purchasing the plated hepatocytes is substantially higher than using human liver microsomes.…”
Section: Albaugh Et Alsupporting
confidence: 90%
“…The longer duration of the testing was due to the limited availability of cells from human donors with acceptable demographics and CYP3A activity. During the course of this study, we observed substantial donor-to-donor variability in CYP3A activity (data not shown), consistent with previous literature (Moore and Gould, 1984). In addition, the cost of purchasing the plated hepatocytes is substantially higher than using human liver microsomes.…”
Section: Albaugh Et Alsupporting
confidence: 90%
“…as due to the presence of neoplastic lesions or other pathological changes in the liver of the five donors. However, primary cultures of human hepatocytes have been shown to display in the amount of DNA damage and repair induced by genotoxic agents a donor to donor variation more marked than that observed in cultures derived from rats (Harris et al 1987;Martelli et al 1988;Butterworth et al 1989), and great interindividual differences have been reported for the metabolism of some carcinogens (Moore & Gould 1984;Butler er al. 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants resulting from eombustion and pyrolysis of organie matter (1)(2)(3). Cells and tissues of various species including man, metabolize a spectrum of PAHs to reactive genotoxic molecules which are potent mutagens and carcinogens (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). PAHs are present in tobacco smoke (18)(19)(20)(21)(22) and may contribute to the development of tobacco related cancers of oral mucosa and contiguous structures (23)(24)(25).…”
mentioning
confidence: 99%